2014
DOI: 10.1371/journal.pone.0109215
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Bedside Assessment of Central Venous Pressure: Scanning into the Future

Abstract: BackgroundNoninvasive evaluation of central venous pressure (CVP) can be achieved by assessing the Jugular Venous Pressure (JVP), Peripheral Venous Collapse (PVC), and ultrasound visualization of the inferior vena cava. The relative accuracy of these techniques compared to one another and their application by trainees of varying experience remains uncertain. We compare the application and utility of the JVP, PVC, and handheld Mini Echo amongst trainees of varying experience including a medical student, interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…All patients underwent a complete cardiac evaluation, including patient history, physical examination, and standard 12‐lead electrocardiogram ECG. The clinical evaluation of jugular venous pressure (JVP) was conducted using a noninvasive bedside technique . All patients underwent primary PCI within 30 minutes, as suggested by the current guidelines .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients underwent a complete cardiac evaluation, including patient history, physical examination, and standard 12‐lead electrocardiogram ECG. The clinical evaluation of jugular venous pressure (JVP) was conducted using a noninvasive bedside technique . All patients underwent primary PCI within 30 minutes, as suggested by the current guidelines .…”
Section: Methodsmentioning
confidence: 99%
“…The clinical evaluation of jugular venous pressure (JVP) was conducted using a noninvasive bedside technique. 4 All patients underwent primary PCI within 30 minutes, as suggested by the current guidelines. 5 Thrombolysis in myocardial infarction (TIMI) flow was visually assessed after PCI by an experienced interventional cardiologist.…”
Section: Study Populationmentioning
confidence: 99%
“…In fact, many researchers have tried to validate this assumption mostly in biventricular circulation and indeed consistently demonstrated significant associations between the 2 pressures. [20][21][22][23] However, correlation coefficients were not high enough, and differences between the 2 pressures were not always small enough to accurately estimate CVP using PVP. 22 In contrast, one previous study performed in patients with single ventricular circulation showed an excellent correlation between the 2 pressures.…”
Section: Peripheral Venous Pressure and Central Venous Pressure Relatmentioning
confidence: 99%
“…4 Medical students after only 10 h of training had a sensitivity of 100% for estimating CVP, whereas cardiology fellows using standard JVP assessment had a lower sensitivity of 86%. 5 Perhaps we need to accept the limitations of JVP assessment, and augment our physical examination with PoCUS. We suggest that PoCUS be integrated into medical curricula and subsequent RACP examinations in order to improve patient care.…”
Section: Clinical Assessment Of Central Venous Pressure: Time For An mentioning
confidence: 99%